Advancing medicine for Alzheimer's disease: A plasma neural exosome platform. Issue 10 (28th August 2020) - Goetzl, Edward J.
Abstract: Enrichment of neurally derived extracellular vesicles of several cell‐types from plasma for protein quantification longitudinally in living patients with Alzheimer's disease has permitted the development of a tentative temporal framework of initiating events, progression mechanisms, and amplification processes. Interactions of beta‐amyloid peptides with an elevated level of their normal prion protein dendritic receptor and of phospho‐tau species with their synaptogyrin‐3 synaptic vesicle receptor replace excessive production and accumulation of neuropathic proteins as the major initiating events. Synaptic dysfunction and microvascular angiopathy are confirmed as early progression mechanisms of decreased neuronal network connectivity, hypoxia, altered blood‐brain barrier, and neurocellular degeneration. Neurally derived extracellular vesicle protein abnormalities also reveal a range of later amplification processes that encompasses insulin resistance, lysosomal defects, decreased survival factors, increased reactive oxygen species, and excessive neuroinflammation. New potential therapeutic targets also are suggested as well as the likely timing of their pathogenic engagement.